2021
DOI: 10.1002/jcsm.12654
|View full text |Cite
|
Sign up to set email alerts
|

Effects of statins on mitochondrial pathways

Abstract: Statins are a family of drugs that are used for treating hyperlipidaemia with a recognized capacity to prevent cardiovascular disease events. They inhibit β-hydroxy β-methylglutaryl-coenzyme A reductase, i.e. the rate-limiting enzyme in mevalonate pathway, reduce endogenous cholesterol synthesis, and increase low-density lipoprotein clearance by promoting low-density lipoprotein receptor expression mainly in the hepatocytes. Statins have pleiotropic effects including stabilization of atherosclerotic plaques, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(92 citation statements)
references
References 161 publications
5
83
0
4
Order By: Relevance
“…Statins decrease the production of coenzyme Q 10 (CoQ 10 ) by inhibiting mitochondrial oxidative phosphorylation and inducing mitochondrial apoptosis [7,54]. Decreased CoQ 10 results in decreased adenosine triphosphate production and energy deficiency.…”
Section: Statinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statins decrease the production of coenzyme Q 10 (CoQ 10 ) by inhibiting mitochondrial oxidative phosphorylation and inducing mitochondrial apoptosis [7,54]. Decreased CoQ 10 results in decreased adenosine triphosphate production and energy deficiency.…”
Section: Statinsmentioning
confidence: 99%
“…Mitochondrial function has been associated with myopathy, which is a side effect of taking statins. Since skeletal muscle is highly energy-consuming and deeply dependent on mitochondrial activity, mitochondrial dysfunction is largely associated with the development of statin-induced myopathy [54]. In a recent meta-analysis examining the effects of CoQ 10 on statin-induced myopathy, the concomitant use of CoQ 10 significantly improved statin-related muscle symptoms, such as muscle pain, muscle cramps, and muscle fatigue [55].…”
Section: Statinsmentioning
confidence: 99%
“…31 However, in in-vitro studies simvastatin directly inhibits L-type Ca 2+ channels in rat pancreatic islet β-cells, reducing activity in the channels, by attenuation of mitochondrial function. 33,35 Compared to normal control cells, simvastatin-treated cells had α lower insulin content, decreased insulin secretion, and less total insulin induced by low glucose level. 34 More recently, it has been suggested that statins may reduce membrane potential by inhibiting mitochondrial complex II activity, which causes oxidative stress.…”
Section: A Statin and The Dysregulation Of The Pancreatic β-Cell Functionmentioning
confidence: 99%
“…For a long time, statins have been prescribed for patients with higher levels of cholesterol, LDL-C, and hypertriglyceridemia in patients with cardiovascular disorders and diabetes [17,18]. However, the current line of evidence has shown that statins have numerous lipid-independent (pleiotropic) actions [19][20][21][22][23][24][25][26]. Among the pleiotropic effects of statins is modulation of autophagy in various cells, providing a promising therapeutic strategy in treating disorders with impaired autophagy as primary underlying pathogenesis [27,28].…”
Section: Introductionmentioning
confidence: 99%